Y‐chromosome haplotype analysis revealing multiple paternal origins in swamp buffaloes of China and Southeast Asia. (8th November 2018) - Wang, Shaoqiang; Xia, Xiaoting; Zhang, Tao; Sun, Ting; Dang, Ruihua; Huang, Yongzhen; Lan, Xianyong; Chen, Hong; Lei, Chuzhao
Abstract: To further probe into the paternal origins and domestication area of swamp buffaloes, we examined Y‐chromosome diversity of 482 bulls representing 22 populations from China and Southeast Asia. A total of 40 bovine Y‐chromosome‐specific microsatellite (Y‐STR) markers were screened in this study. The results showed that seven Y‐STR markers (UMN2405, UMN0504, UMN0103, UMN1307, BC1.2, UMN0304 and INRA008) were specific and polymorphic in male swamp buffaloes, which can define 9 Y‐haplotypes corresponding to four Y‐haplogroups (Y1, Y2, Y3 and Y4). Haplogroup Y1 was predominant (83.4%) in all swamp buffalo populations, indicating haplogroup Y1 was the major domestication event of swamp buffalo. In addition, the abundant genetic background and backbone of haplogroup Y1 suggested Yangtze Valley as the major domestication area of swamp buffalo. Interestingly, haplogroup Y4 was only confined in Hainan Island which was more ancient than other haplogroups. We hypothesized that haplogroup Y4 was the descendants of the wild Asian buffalo trapped on Hainan Island in prehistoric glacier period and preserved by later introgression into domesticated cows after the domestication. In conclusion, our findings revealed four divergent paternal origins in swamp buffaloes based on Y‐STR markers.